1987
DOI: 10.1037/0735-7028.18.1.61
|View full text |Cite
|
Sign up to set email alerts
|

Clinician attitudes toward time-limited and time-unlimited therapy.

Abstract: His research and training interests include time-limited individual and group psychotherapy. JAY A. BKIIRMAN. MS. is a research associate at the Comprehensive Clinic. Brigham Young University, where he serves as a research design and statistical consultant. He also teaches statistics and mathematics at University ofUtah. His research interests include remedial and preventative educational and psychological intervention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
10
0

Year Published

1990
1990
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 6 publications
1
10
0
Order By: Relevance
“…More specifically, counselors may prefer open ended treatment because of its greater opportunities to work toward insight and personality reconstruction, while clients themselves may be content with TLP because it helps them feel better rapidly (Johnson & Gelso, 1980). In another survey, Burlingame & Behrman (1987) pointed out that TLP was perceived as more efficacious by therapists in cases of situational adjustment reactions, but the therapists favored unlimited treatment over TLP for several other diagnoses such as neurotic depression, psychosis and personality disorders. The researchers suggest that therapists often see TLP as a crisis intervention, therefore being more applicable to disorders such as a situational adjustment disorder.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…More specifically, counselors may prefer open ended treatment because of its greater opportunities to work toward insight and personality reconstruction, while clients themselves may be content with TLP because it helps them feel better rapidly (Johnson & Gelso, 1980). In another survey, Burlingame & Behrman (1987) pointed out that TLP was perceived as more efficacious by therapists in cases of situational adjustment reactions, but the therapists favored unlimited treatment over TLP for several other diagnoses such as neurotic depression, psychosis and personality disorders. The researchers suggest that therapists often see TLP as a crisis intervention, therefore being more applicable to disorders such as a situational adjustment disorder.…”
Section: Resultsmentioning
confidence: 99%
“…Although TLP clients seemed to be satisfied with their counseling in general, multiple studies found them to be less satisfied with the length of treatment. Less well-adjusted, more chronic clients may do better in open-ended therapy than in TLP.Phelps, Eisman, & Kohout (1998)TQuantitative Questionnaires Variety of therapeutic orientationsMajority of psychologists indicated managed care (including time limited facet) had a negative impact on their practices.Burlingame & Behrman (1987)TMeta-analysis (36 studies) Clinician reports, Client reports, QuestionnairesTLP was perceived as more efficacious by therapists in cases of situational adjustment reactions, but they favored unlimited treatment over TLP for several other diagnoses.Murphy, Debernardo, & Shoemaker (1998)TQuantitative Questionnaires N = 180Majority of clinicians in a managed care setting indicated that putting limits on the number of sessions interfered with their treatment.Cohen, Marecek, & Gillham (2006)TQualitative Semi-structured interviews (N = 18) Variety of therapeutic orientations2/3 of the therapists in a managed care setting indicated that the lack of control over the length of treatment was an obstacle to its successfulness. Time constraints made them alter their therapeutic approach.Wright, Simpson-Young, & Lennings (2012)TQuantitative (n = 85) & Qualitative (n = 27) Questionnaires & Interviews Mostly CBT-therapistsTherapists in a managed care setting felt their therapeutic approach was impacted by time limits and they worked more superficial in a time limited treatment.Busch et al (2001)TQualitative (N = 6) Psychoanalytic therapistsThe time limit created pressure for therapists in a research setting, which had its up and downsides.Dekker et al (2005)P, AQuantitative Questionnaires (N = 103) Short Psychodynamic Supportive Therapy43% of patients thought there were not enough therapy sessions.…”
mentioning
confidence: 99%
“…A number of clinical (Budman & Gurman, 1988;Hoyt, 1990;Steenbarger, 1992a) and survey (Burlingame & Behrman, 1987) reports have identified substantial practitioner skepticism over the therapeutic potential of BT. Nevertheless, both research and practice literatures suggest that meaningful and enduring change can occur within the context of brief-and sometimes very brief-interventions (Steenbarger, 1992b(Steenbarger, , 1993b.…”
Section: Duration and Outcome In Psychotherapymentioning
confidence: 99%
“…The content analysis gives further support to these findings. Burlingame and Behrman (1987), based on the Therapist Attitude and Experience Inventory, also report that therapists believed that ST was more efficacious than LT in treating adjustment disorders and less efficacious in treating all other diagnostic groups. Respondents seem to disagree with those; for example, Clarkin and Frances (1982) who recommend ST for more disturbed patients.…”
Section: Discussion and Applications To Social Work Practicementioning
confidence: 93%